ISLAM DAN FUNDAMENTALISME: ANALISIS AYAT AL-QUR’AN TENTANG FUNDAMENTALISME DALAM ISLAM: (Kajian Tafsir Maudhu’i) - Krisnia, Mia; Yunior, Muhammad Alga; Rayhan, Muhammad Gilang; Maulana, Muhammad Rizka; Muhyi, Asep Abdul (Prodi Ilmu Al-Qur'an dan Tafsir, 2023)
This study intends to examine the understanding of fundamentalism that exists in society as one of the discussions on contemporary issues in the Islamic religion using the perspective of maudhu'i interpretation in the Koran. The research method that we used in writing this research is a qualitative method, namely by collecting accredited journals to serve as references and reading material and taking references to several reliable sources. To interpret the verse we use the thematic interpretation method, namely by searching for the word to be interpreted, then looking for the intended theme of the verse and presenting the verse and its translation and writing the asbabun nuzul and its interpretations. Beginning with choosing words in the Koran that are in accordance with meanings that are close to fundamentalism, then studied and examined using maudhu'i interpretations. This research presents and describes the problems of Muslims who still use fundamentalism and do not want to open themselves to other than their group, as well as people who understand religion rigidly and are fixated on texts alone.